Designing an Integrated Curriculum Based on Local Primacy and Social Reconstruction Perspectives of West Nusa Tenggara, Indonesia (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The purpose of this study was to develop a curriculum model which included local primacy based on the principles of social reconstruction curriculum in West Nusa Tenggara. This study was a developmental research which adopted and modified Borg Gall developmental model (1983) with the following stages: (1) needs analysis; (2) model development; and (3) model validation. The results of needs analysis indicated that coral reef materials were the main priority of local primacy integrated into the secondary school curriculum in West Nusa Tenggara. The principles of social reconstruction curriculum were implemented in three components as the result of model design, i.e. learning objectives, learning methods (organizational learning strategies, learning delivery strategies, and learning management strategies), and learning results or assessment. The product design model was embraced in instructional tools consisting of syllabus, topic formulation and basic competence, comic learning materials, and assessment instruments. Based on the assessment qualifications on the instructional tools validation test which included three aspects, namely the content aspect, the display aspect and the accuracy aspect of language use, the mean scores were 3.4, 3.8, and 3.4 respectively. Therefore, the overall instructional tools were in a very good category.Â